Ecofriendly Neem Coated Urea A boon for farmers - Meena, B P; Biswas, A K; Shirale, A O; Ramesh, K; Jha, P; Lakaria, B L (Indian Farming, 2018)
NCU is an eco-friendly and best way for enhancing crop yield, NUE and safeguarding the environment through minimizing nitrification and volatilization losses. NCU improves the effectiveness of urea in supplying nitrogen to crop plants and reduce the urea requirements by 20% hence saving of ` 6000 crore in subsidy annually. Besides, N supply, NCU also adds secondary benefits by reducing infestation of large number of pests and insects. NCU may also prevent illegal diversion of subsidized urea to industry and other nonagricultural sectors thus saving government exchequer. Considering overall benefits of NCU in agriculture the government is emphasizing more on use of NCU fertilizer in India.